A non-destructive technique for health assessment of fire-damaged concrete elements using terrestrial laser scanning - Mukupa, Wallace; Roberts, Gethin Wyn; Hancock, Craig M.; Al-Manasir, Khalil (Springer, 2016)
Concrete structures are routinely monitored to detect changes in their characteristics in the field of engineering surveying and other disciplines such as structural and civil engineering. There is growing demand for the development of reliable Non-Destructive Testing (NDT) techniques for concrete structures in the assessment of the deteriorating condition of infrastructures or in an event of fire-damaged structures. In this paper, the feasibility of using Terrestrial Laser Scanning (TLS) technology for change detection and assessment of fire-damaged concrete has been investigated through measurements and analysis of laboratory size concrete specimens that underwent heating up to 1000°C. The TLS technique employed in detecting fire-damaged concrete involved modelling and analysis of the TLS intensity returns as well as RGB image analysis. The results obtained clearly demonstrate the feasibility of using TLS to detect fire-damaged concrete. Although the laser scanners used in the study have different wavelengths, the results obtained in both cases are promising for a detection technique of fire-damaged concrete structures.